The anthropomorphic pursuit of AI-generated journalistic texts: limits to expressing subjectivity - González-Arias, Cristian; Chatzikoumi, Eirini; López-García, Xosé (Frontiers in Communication, 2024)
The anthropomorphization of language developed by artificial intelligence tools is a field of growing interest, especially as applications incorporating conversational tools based on language models (LLMs) are refined. It is essential to understand the capabilities and limitations of these AI tools in imitating human language, both from a grammatical and pragmatic perspective. In this research, we have focused on communication in the journalistic field, although this analysis and reflection are relevant in all areas of application for generative tools. The imitation of human language by AI machines has technical, communicative, and ethical implications. With this work, we hope to contribute in some way to this discussion.